Enforcing Replica Determinism in the Road Side Units of Fault-Tolerant Vehicular Networks - Almeida, João
This paper presents a strategy to enforce replica determinism in the road-side units (RSUs) of wireless vehicular networks. An active replication scheme is used to enhance fault-tolerant behaviour in these RSU nodes, which are responsible for handling channel access and admission control policies in real-time vehicular communications protocols. The proposed solution guarantees consistency among all RSU replicas, by introducing a dedicated link shared exclusively by these units, allowing them to implement an atomic commit protocol of the packets received through the wireless medium. This strategy also has the advantage of reducing packet loss, since only one replica needs to successfully decode the packet in order for it to become available to the RSU group of replicas. It should be noticed however that this method increases the total delay of packet delivery to the upper layers of the communications protocol, so its impact on the real-time properties of the network needs to be further evaluated.